Development of Laboratory Management Based on Local Bali Wisdom to Improve The Quality of Services In Laboratory - Lasia, I Ketut (JPI (Jurnal Pendidikan Indonesia), 2017)
This study aims to develop laboratory management model based on Bali local wisdom to improve quality of laboratory service. This research is the development research by adopting of research and development model in education. Limited scale trial was conducted on 50 students from the Chemistry Department of Education, Ganesha University of Education year 2016 with a class action research model of Kurt Lewin. Fifty students were comprised of 7 groups of physical chemistry practicum and 7 groups analytical chemistry practicum. The instrument of this study was observation sheets and questionnaires. Observations and questionnaires were analyzed descriptively. Results of the study are: Bali local wisdom relating to the laboratory management, a laboratory management model based on Bali local wisdom to improve quality of laboratory service, a laboratory management model was developed very effective, the model can be applied, and the student response to the laboratory management model is very positive.